The Debate Over Nasakh in the Verse of Bequest: An Analysis of Shaykh Muhammad Abduh’s Thought in Tafsir al-Manar - Nasution, Khairul Bahri; Irfan, Rengga; Saputra, Edriagus (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
This research explores Shaykh Muhammad Abduh's views on the pros and cons of the will verse, which is generally considered by the majority of scholars to have been abrogated by the inheritance verse or the Ahad hadith. It also examines his contribution to the re-interpretation of Islamic inheritance law across different religious contexts. This study is qualitative library research, focusing on Muhammad Abduh's interpretation of the will verse in his al-Manar commentary, linking his ideas to contemporary legal decisions. Secondary data sources include books, articles, journals, and relevant internet materials. The findings reveal that, according to Abduh, the will verse remains valid (muhkam), specifically for those who do not inherit from their relatives. He argues against the claim of abrogation (nasakh) for several reasons: First, the context of the verse contradicts nasakh, emphasizing that the will must take priority over inheritance. Second, the verse regarding inheritance applies specifically to non-heirs, including those excluded due to religious differences. Third, the Salaf permitted bequests to heirs, provided they were given to those in need. Fourth, the hadith